Chemically Diverse S. mansoni HDAC8 Inhibitors Reduce Viability in Worm Larval and Adult Stages. (8th November 2022) - Noce, Beatrice; Di Bello, Elisabetta; Zwergel, Clemens; Fioravanti, Rossella; Valente, Sergio; Rotili, Dante; Masotti, Andrea; Salik Zeya Ansari, Mohammad; Trisciuoglio, Daniela; Chakrabarti, Alokta; Romier, Christophe; Robaa, Dina; et al.
Abstract: Schistosoma mansoni HDAC8 is a reliable target to fight schistosomiasis, and several inhibitors have been reported in the literature up to now. Nevertheless, only a few displayed selectivity over the human deacetylases and some exhibited very low or no activity against parasite larvae and/or adult worms. We report here the in vitro enzyme and biological activity of a small library of HDAC inhibitors from our lab, in many cases exhibiting submicromolar/nanomolar potency against smHDAC8 and diverse degrees of selectivity over hHDAC1 and/or hHDAC6. Such compounds were tested against schistosomula, and a selection of them against the adult forms of S. mansoni, to detect their effect on viability. Some of them showed the highest viability reduction for the larval stage with IC50 values around 1 μM and/or displayed ∼40–50 % activity in adult worms at 10 μM, joined to moderate to no toxicity in human fibroblast MRC‐5 cells. Abstract : Epigenetic drugs : The HDAC inhibitors 2 and 7 –9 significantly decrease the viability of S. mansoni in both larvae and adult worms, and show moderate (7 ) or no (2, 8, and 9 ) toxicity toward human fibroblast MRC‐5 cells. At the enzyme level, compounds 2, 7, and 9 exhibit high smHDAC8 inhibitory activity along with a degree of selectivity, whereas 8 shows lower activity OK